POTENSI ANTIOKSIDAN REBUSAN DAN SEDUHAN TEMU MANGGA (Curcuma mangga) DENGAN METODE DPPH - Halimah, Nur; Sa'ad, Muhammad (BENZENA Pharmaceutical Scientific Journal, 2025)
Background : Free radicals are unstable molecules that cause oxidative stress and various chronic diseases. Antioxidant compounds can play a role in neutralizing free radicals. Plants as natural ingredients of traditional medicine contain secondary metabolite compounds that act as antioxidants. One of the plants used as an antioxidant is temu mangga (Curcuma mangga). The use of natural ingredients as medicine by the people in Indonesia mostly uses the boiling and steeping methods. Objective : This study aims to determine the antioxidant activity of boiled and brewed temu mangga rhizome (Curcuma mangga) compared to quercetin. And to determine the content of secondary metabolites that are responsible for antioxidant activity. Method : Phytochemical screening using color reagents to determine the content of secondary metabolites including: alkaloids, tannins, saponins, and flavonoids. Antioxidant activity was measured using the DPPH method using the parameter of the Inhibitory Concentration 50% (IC50) value with quercetin as a positive control. Result : The results showed that both methods have secondary metabolite compounds that are responsible for antioxidant activity, namely: alkaloids, tannins, saponins, and flavonoids. Both methods showed very strong antioxidant activity, with IC50 quercetin, boiling and brewing method respectively of 5.62 ppm; 5.75 ppm; and 5.53 ppm. The brewing method was slightly more effective, possibly because the temperature used was lower, thus maintaining the stability of thermolabile antioxidant compounds such as flavonoids. Conclusion : Extraction method has significant effect on antioxidant activity. The brewing method can be a more optimal traditional method to maintain antioxidant properties of Curcuma mangga.